Penilaian Keamanan Informasi Menggunakan Pendekatan Indeks Keamanan Informasi 4.0 dan Vulnerability Asessment - Juliharta, I Gede Putu Krisna; Erawan, Ayu Pradnyandari Dananjaya (LPPM STIKOM Tunas Bangsa, 2024)
In the era of rapidly evolving information technology, information security has become increasingly crucial. Threats to data and information are becoming more diverse and complex, making information security preparedness the key to protecting an organization's critical assets. XYZ City, with its commitment to optimizing the use of information technology, recognizes the importance of information security. Therefore, the Information and Communication Technology Office (Diskominfo) of XYZ City conducted an assessment using the Information Security Index (KAMI) to measure, analyze, and improve the maturity of information security in its organization. The results of the KAMI assessment indicate that XYZ City has achieved a good evaluation result. While there are some areas that show good performance, such as Risk Management and Technology and Information Security, there are still areas that need to be strengthened.